Innovative direction of the professional training of future masters of physical culture and sports - Yevtyfiiev, Andrii Sergiyovych (Impressum, 2024)
Physical culture and sports is an industry, the specificity of which is the organization and conduct of various health and sports events. However, such training of future specialists in physical culture and sports is not given sufficient attention in the practice of modern higher education in Ukraine. The article substantiates that special attention should be paid to the preparation for the organization of health and sports events at the level of master's training of future specialists in physical culture and sports. The future Master of Physical Culture and Sports as a future organizer is defined as a person who, as part of the organizing committee (team), including as an initiator, will be able to organize all the necessary actions and elements that ensure the preparation and conduct of health and sports events. The article identifies similarities and differences in the organization of events for professional athletes and the general public. In accordance with the need to solve the problem formation ofreadiness of future masters of physical culture and sports for the organization of health and sports events, innovative directions of such training are presented.
Keywords: organization; future masters of physical culture and sports; health and sports events